The Description Of Post-Dural Puncture Headache In Post-Caesarean Section Patients Undergoing Spinal Anaesthesia At RSUD Cilacap - Annisa, Rully; Purwanti, Putri Wahyu (Universitas Muhammadiyah Kalimantan Timur, 2025)
The high maternal mortality rate associated with childbirth remains a critical concern in the healthcare sector. One method employed to address delivery complications is the caesarean section. However, the use of spinal anaesthesia in this procedure can result in complications, including Post dural puncture headache (PDPH). PDPH can affect patients' postoperative activities and recovery, necessitating a deeper understanding of its incidence and contributing factors. This study aims to describe the incidence of PDPH in post-caesarean section patients at Cilacap Regional Public Hospital, as well as to understand the factors affecting the occurrence of PDPH and the pain levels experienced by patients postoperatively. A quantitative appchach with a descriptive design was utilized in this study. The research sample comprised post-caesarean section patients who received spinal anaesthesia at the hospital. Data were collected through direct observation and interviews, using observation sheets and the Numerical rating scale (NRS) to measure pain levels. The results indicated that among the total patients who underwent caesarean section with spinal anaesthesia, a portion experienced PDPH with varying pain levels. Specifically, 17 respondents (56.7%) experienced PDPH, while 13 (43.3%) did not. Factors influencing the occurrence of PDPH included age, body mass index (BMI), number of punctures, needle size, and previous history of PDPH. This study concludes that the incidence of PDPH in post-caesarean section patients is significant, with certain factors contributing to the risk of developing PDPH. The findings of this research contribute to a deeper understanding of PDPH complications in post-caesarean section patients and provide a basis for future research development in this field.